Diseño e implementación de un terminal de consultas electrónica para la ciudadanía en la Municipalidad del cantón Saraguro. - Tocto Torres, Carla Maribel (2010)
The present Project describes Design e implementation of a terminal electronic report with Touch Screen technology that will find ready in a public place for the citizenship in the municipality of the Canton Saraguro, it take root in the automatization of daily task to inform the citizenship of economic, social and tourist management that leads the municipality. This automation aims to support the change process to inform the citizen implementing new technology. Five informative modules are included in the project: Municipality, tourism, revenue, services and economic reports. The system searches both support users in the data report as to municipality to expedite the delivery of information to the people. The project was developed using four SQLyog Enterprise 8.5, Hibernate, and free software tools, these are relational database handle, and NetBeans IDE 6.8 and Report 3.0.0 development tools. The system facilitates access to information and streamlines the process input allowing its distribution. These tools known as reliable and robust in its use and allow for a simple way using the application they chose. Security system was designed and implemented according to the current needs of the institution is based on security settings provided by the handle database and application development. The methodology for carrying out the project is the sequence of a system development life cycle, this cycle consists of seven phases that begins with the identification of the problem and ends with the implementation, and evaluation system. Analysis, design and development of the system are based primarily on the use of class modeling, database diagram and deployment diagrams.